Fashion meets socialism : fashion industry in the Soviet Union after the second world war (2016)
Fashion and design would, in the West, commonly be seen as antithetical to the values of Soviet society. Awareness was, and is, high in relation to the accomplishments of the Soviet Union in the area of scientic progress in the late 1950s and early 1960s and even the leading powers in the West looked on sputniks and cosmonauts with envy and admiration. At that time overall economic growth in the USSR was quite impressive, and its leaders’ pompous statements about overcoming the production levels of the USA in many basic industrial products and food-stus did not seem at all farfetched. What was less generally known however was that, during this period, the Soviet Union made major investments in fashion design. Promoting fashion and improving the standards of clothing was as important as the general politics of material culture in the Soviet Union. e Soviet Union has certainly never enjoyed a high reputation in the world of fashion. e standardized, industrially mass-produced clothes were held in low esteem by both Soviet consumers and foreign visitors. If anything, Soviet citizens were generally dissatised with the domestic supply of clothing. To foreign visitors, street fashion in Moscow, not to mention smaller provincial towns or the countryside, looked rather dull, uniform and grey. Interestingly at this time, the Soviet Union had one of the world’s largest organizations of fashion design, all planned, nanced and supported by the state. ousands of professional, well-educated designers worked in the various Soviet institutions of fashion. ey designed according to the annual plan thousands of new fashionable garments and accessories both for industrial mass production and for smaller fashion ateliers that sewed custom made clothes for their customers.